World-system analysis in the methodology of theoretical jurisprudence - Kalinin, Sergey A. (Journal of the Belarusian State University. Law, 2020)
The author of the article substantiates the idea of the necessity to expand the methodological apparatus of jurisprudence by cognitive phenomena that allow us to consider the state and law as historical and dimensional elements of external social systems. The thesis that the world-system analysis concept, which arose within the framework of neo-Marxism and is presented in Russian-speaking post-Soviet science by two main directions, representing both the development of ideas of Western scientists and their own conceptual research, meets these requirements, is put forward. The initial methodological axioms are described, and the heuristic potential of the world-system analysis is also described.
Keywords: methodology of jurisprudence; world-system analysis; liberal geoculture